Análisis descriptivo del estado de salud en los adultos mayores de la parroquia la Carolina - Imbabura - Cachiguango Campo, Edén Stefanny (2024)
The study focuses on the application of the Comprehensive Geriatric Assessment Spheres (VGI) of older adults in the La Carolina community, Imbabura, Ecuador, during the period October 2023 - February 2024. The VGI is a fundamental tool to evaluate health and quality of life of this population group, allowing the identification of needs and risks for timely intervention. The objective of the research was to describe the health status of older adults in the La Carolina community. To this end, these VGI scales were applied to a sample of 72 older adults, using probabilistic sampling. The results of the study indicate that the older adult population studied in the La Carolina community is predominantly female, the level of education is low and they perform physical activities independently. Regarding mental health, no signs of depression were found, but a high social risk was found due to socioeconomic conditions. This study provided valuable information that will be used in the future for the development of health promotion and disease prevention interventions in the older adult population of the La Carolina community. From this research, it is concluded that the Comprehensive Geriatric Assessment is a useful tool to evaluate the comprehensive health of older adults and the identification of early health problems, which can help prevent adverse events and improve the quality of life of this vulnerable population.